A Descriptive Study on Sepsis: Causes, Outcomes, and Adherence to Guidelines on Patients with Sepsis at a Tertiary Care Hospital in Sri Lanka. (15th July 2020) - Matthias, Anne Thushara; Indrakumar, J.; Ranasinghe, Tharushi; Wijekoon, Shalini; Yashodara, Charuni
Abstract : The global incidence of sepsis is increasing, and mortality remains high. The mortality is even higher in resource-poor countries where facilities and equipment are limited. The Surviving Sepsis Campaign ( SSC ) recommends an updated hour-1 bundle based on the evidence from the International Guidelines for Management of Sepsis and Septic Shock 2018. To reduce mortality from sepsis, compliance with the "bundle" is essential. Data from developing countries like Sri Lanka on the management of sepsis according to the SSC guidelines are not available. Hence, this study looks at the patient characteristics and management of septic patients at a tertiary care hospital in Sri Lanka. Patients admitted to the University Medical Unit of Colombo South Teaching Hospital from January to August 2019 fulfilling the inclusion criteria were included. The hour-1 sepsis bundle adherence, demographic data, and management were recorded. There were 387 patients: 163 males and 224 females. The age range was 15-95 with a mean age of 63. 83.7% were direct admissions while 16.3% were transfers from a peripheral hospital. The most common source of infection was urine (82 (21.2%)) followed by blood stream (105 (27.1%)) and skin and soft tissue (114 (29.5%)). One-hour SSC bundle compliance is as follows: administration of intravenous fluids: 42 (10.9%), blood cultures before antibiotics: 225 (58.1%), first dose antibiotic: 15 (3.9%), and arterial blood gas: 60 (15.5%). Staffing capacity did not make a difference to adherence to the bundle. The study mortality rate was 37 (9.6%). Binary logistic regression indicates that quick sequential organ failure assessment (qSOFA) score is a significant predictor of mortality (chi ‐ square = 35.08, df = 3, and p = 0.001 (<0.05)) with an odds ratio (OR) of 7.529 (95% CI 3.597-14.323). The other predictors, age, sex, adherence to sepsis care bundle, and comorbidities, were not significant. In conclusion, mortality of sepsis is high and adherence to sepsis care bundle is poor in Sri Lanka even at a tertiary care hospital. Education and training of staff are needed to boost adherence. This will in turn improve quality of care and outcomes of septic patients in resource-poor countries.